Oxidation of microcystin-LR and cylindrospermopsin by heterogeneous photocatalysis using a tubular photoreactor packed with different TiO2 coated supports - Lívia X. Pinho (2015)
The photocatalytic degradation of cyanotoxins in aqueous solutions using slurry suspensions of TiO2 implies a post-filtration step to retain the photocatalyst. In this work, 2D and 3D TiO2 thin films supported in inert surfaces was proposed for the solar photocatalytic removal of cyanotoxins microcystinLR (MC-LR) or cylindrospermopsin (CYN) in distilled and natural water under neutral pH conditions. The photocatalytic experiments were performed in a lab-scale tubular photoreactor with a compound parabolic collector (CPC) using simulated and natural solar radiation. The tubular photoreactor was packed with transparent cellulose acetate monoliths (CAM) coated with a P25 paste or sol-gel 2D TiO2 film or with a photocatalytic 3D TiO2-loaded exterior paint (PC500, VLP7000 and P25). The efficiency of the TiO2 photocatalytic system in the presence of hydrogen peroxide was also assessed. PVC or glass tubes and glass spheres, coated with a photocatalytic 3D TiO2-loaded exterior paint, were also tested as inert surfaces. The supports used in this work were chosen according to some characteristics, such as cost, surface resistance, surface area and transmissibility to UV radiation. The toxins MC-LR and CYN were purified from Microcysts aeruginosa and Cylindrospermopsis raciborskii cultures, respectively. The photocatalytic system P25-CAM/H2O2 can be considered the most effective process, considering the cyanotoxins removal efficiency, the cost and the simplicity of the preparation.